Analysis of dietary with hydroponic forage in fattening cattle in the Jiramena, village of San Carlos de Guaroa, Colombia (Revista Sistemas de Producción Agroecológicos, 2013)
The present research evaluated the production of steers of this region as it is not allowing to generate a return that succeed in improving the living conditions of the residents, because there is no adequate feeding and handling of animals in order to maintain an appropriate amount won to generate the desired utilities. By analyzing information found that steers producers spent more than five years working on this land and who are developing this farming activity as important for economic screed, but that being extensively is not providing revenue necessary to meet their needs. This could be determined because the activity does not have any livestock modernization, representing the mismanagement of development of production and hence food that is given to cattle. The results also showed that cattle producers not fattening food supplement with another animal fodder, so only use pasture fields arising from own and that is why livestock is extended, which added to the lack of knowledge about food supplementation and little support from the state, formed an adverse situation that affects the development of the region. On the other hand, there are no defined teams and adequate infrastructure for handling cattle, so in many cases are low in the number of livestock, decreasing revenues worsening the situation of people. When comparing bromatological traditional grazing grasses and hydroponic forage production (FVH) as an alternative to improve the feeding process, it was found that the protein content of the fifteenth day is 18.22%, which contributes to improve the animal's weight at 677 grams, a significant percentage towards improved animal weight in less time and also to have more livestock on small plots as these producers, which will lead to increase revenue. Developing assembly building for the production of FVH conclusion could be reached with the financial evaluation and its parameters to it as V.P.N., T.I.R, RB/C, and the sensitivity analysis considering a chance rate of 12%, which is profitable to invest in a project of this nature because it is making a return rate of 32%, which means that the producer must improve their production conditions to achieve higher revenues. Therefore, the FVH enables the farmer to have a forage in the desired quantity as needed, with high quality and value still substantially cheaper than conventional feed, thus replacing large areas of land that are essential for forage, creating competitive farms of small size and high yields in areas where the soil and climate are adverse.
Keywords: hydroponic green fodder; cattle fattening; feeding; nutritional supplement